The flame trees of Thika [videorecording (DVD)] - Baker, Roy; Mills, Hayley; Robb, David, 1947-; Nicholas, Jones, 1946- (A & E Home Video ; New Video, 2005)
A young girl and her parents journey to the unspoiled wilderness of East Africa in 1913 where they struggle to transform a rugged plot of land into a farm.